2014
DOI: 10.1113/jphysiol.2013.269597
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ionotropic glutamate receptor function by vertebrate galectins

Abstract: Key pointsr Lectins are a family of small evolutionarily conserved sugar-binding proteins that regulate a diverse array of physiological processes ranging from immune system activation to cancer cell metastasis.r Ionotropic glutamate receptor function can be modulated by plant-derived lectins, but the physiological relevance of this activity is unclear as no analogous function has been identified in animal lectins.r We found that a variety of vertebrate lectins, including human brain-expressed galectin-1, modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…In humans, AMPAR subunits GluA1-4 each have several N -glycosylation sites that exert regulatory effects on glutamate-signaling. Specific N -glycans expressed on AMPAR subunits modulate neurotransmission by influencing receptor assembly, trafficking, and synaptic stability, as well as by amending interactions between receptors and activity-modulating compounds (Copits et al, 2014; Everts et al, 1997; Kawamoto et al, 1994; Pasternack et al, 2003; Standley et al, 1998; Standley and Baudry, 2000; Takeuchi et al, 2015). N -glycosylation of N370 in GluA2 is necessary for the ER exit of GluA2 as well as the cell surface expression of both GluA2 and GluA1; furthermore, when a specific glyco-epitope (the HNK1 epitope, a unique N -glycan terminal trisaccharide) is expressed on GluA2 N413, both GluA1 and GluA2 demonstrated increased cell surface expression (Takeuchi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, AMPAR subunits GluA1-4 each have several N -glycosylation sites that exert regulatory effects on glutamate-signaling. Specific N -glycans expressed on AMPAR subunits modulate neurotransmission by influencing receptor assembly, trafficking, and synaptic stability, as well as by amending interactions between receptors and activity-modulating compounds (Copits et al, 2014; Everts et al, 1997; Kawamoto et al, 1994; Pasternack et al, 2003; Standley et al, 1998; Standley and Baudry, 2000; Takeuchi et al, 2015). N -glycosylation of N370 in GluA2 is necessary for the ER exit of GluA2 as well as the cell surface expression of both GluA2 and GluA1; furthermore, when a specific glyco-epitope (the HNK1 epitope, a unique N -glycan terminal trisaccharide) is expressed on GluA2 N413, both GluA1 and GluA2 demonstrated increased cell surface expression (Takeuchi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the differences in the expression of the native GluN subunits and/or specific protein complexes regulating the assembly, ER retention, and/or intracellular trafficking of NMDARs among the various cell types could account for this phenomenon. Interestingly, recent studies reported that the N-glycosylation pattern of AMPA receptors in the cortex is altered in schizophrenia (42), the ionotropic glutamate receptor function is modulated by vertebrate galectins (43), and O-GlcNAcylation of the GluA2 subunit is associated with long-term depression in hippocampal synapses (44). Therefore, it is likely that future studies will reveal more information regarding the precise roles that specific glycosylation of NMDARs play in regulating neuronal function.…”
Section: Discussionmentioning
confidence: 99%
“…Now, a study from Geoff Swanson's lab in this issue of The Journal of Physiology (Copits et al . ) investigates the ability of vertebrate galectins, including recombinant human galectin‐1, and congerin I and II from the conger eel, to regulate native and recombinant AMPA and KA receptors. Galectins bind specifically to β‐galactoside glycoconjugates and the three galectins studied by Copits et al .…”
mentioning
confidence: 99%
“…Galectins bind specifically to β‐galactoside glycoconjugates and the three galectins studied by Copits et al . () can each form a bivalent homodimer. In contrast to tetravalent ConA, which substantially increases currents mediated by most AMPA and KA receptor isoforms, galectin application produced a remarkable diversity of effects on recombinant iGluRs depending on the specific subunits that were expressed and on which galectin was applied.…”
mentioning
confidence: 99%
See 1 more Smart Citation